Debt Equity Conversions and NPL Securitization in China : Some Initial Considerations - Daniel, James (Technical Notes and Manuals; Technical Notes and Manuals, 2016)
This note considers the role debt-equity conversions and NPL securitization can play in addressing excessive corporate debt in China, and the corresponding burden on banks of impaired assets. It finds that such techniques can play a role, but getting their design right is critical, as is nesting them within a comprehensive, system-wide, plan.